Estimation of Pitch and Fundamental Frequency Variation Between Normal Males, Females and Intersex Population - Akashlina Basu1 , Pooja Ahuja1, M. S. Dahiya3 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Human beings have certain uniqueness in their voices that helps determine their individuality. The most important characteristic of voice is the Pitch. The average vocal range for masculine voice ranges from 90- 150 Hz and for feminine voice, it ranges from 190-240 Hz. This pitch is decided by the development of the vocal tract during puberty by the effect of testosterone hormone i.e. Longer the tract, lower the pitch and vice versa. However, for people belonging to the intersex community, the low production of testosterone causes the vocal tract to develop differently than males and females. Because of this reason, their pitch has its own individual range and hoarseness of quality. This study was aimed to evaluate the difference in intersex population voice characteristics as compared to normal adult males and females. It was found that intersex voice has a distinctive Pitch range of 150-190 Hz with the mean frequency being 167 Hz. It was also discovered that due the peculiar dialect practiced by the intersex community, especially in the western part of the Indian subcontinent, there is a noticeable difference in the time duration for pronouncing various vowels from the time duration taken by males and females to pronounce the same vowels.